Comparative histology of the vocal sac in three species of hylid frogs with comments on its functional correlates - Ferreira Bueno, Natalia (2023)
The vocal sacs of frogs are elastic structures responsible forthe circulation of air during vocalization, amplifying the sounds produced by these animalsduring multimodal communication. Vocal sacs present a wide array of morphologiesamong species and may be single, paired, or absent in adult males. Most studies on vocalsacs in Anura deal with their external morphology, and not with their internal structure,which has been explored in only a handful of species. The aim of this study was to assessvocal sac structure in three hylid species, Dendropsophus haddadi, D. elegans, and Scinaxfuscovarius, using histological techniques. These species differ greatly in the degree ofdevelopment and histological properties of the gular skin and submandibular musculature.In particular, elastic fibers are abundant in the thick m. interhyoideus and the relativelytight gular skin of S. fuscovarius. In contrast, in both species of Dendropsophus (althoughmore evident in D. elegans), the m. interhyoideus is extremely thin and expanded, with anegligible number of elastic fibers that appear as a loose, pleated sheet when deflated. Weanalyzed videos of calling males of the three species and their close relatives, which showtwo different patterns of inflation/deflation. These patterns are strongly correlated with thehistological properties of the vocal sac wall. The three species have different vocal sacshapes and rely differently on elasticity for vocal sac function.